Psychometric Evaluation of the Persian Version of Religious Orientation Scale in Iranian Patients with Cancer - Sharif Nia, Hamid (Journal of religion and health, 2021)
This paper reports on the psychometric properties of the Religious Orientation Scale (ROS) with a sample of 311 Iranian patients who were suffering from cancer between September and December 2020. A cross-sectional study design was used, and convenience sampling was employed. Reliability was evaluated by internal consistency Cronbach’s alpha, McDonald’s omega, and average inter-item correlation. The exploratory factor analysis showed that the ROS had 15 items and two factors (religious identity and personal identity) that explained 43.2% of the total variance of religious orientation in Iranian patients with cancer. Construct validity was assessed by means of confirmatory factor analysis. The internal consistency and composite reliability were acceptable. The results indicate that the ROS can produce reliable and valid data on religious orientation in a sample of Iranian patient with cancer.